Influence of power qualityon the reliability of heat network equipment - Alisultanov, Timur (National Technical University "Kharkiv Polytechnic Institute", 2024)
This essay, focusing on the theme of a dissertation, delves into the intricate relationship between power quality and the reliability of heat network equipment. Through an exhaustive review of scholarly literature, including journal articles, conference papers, and government reports, as well as an indepth analysis of methodologies and data, the study examines the impact of power quality variations on the operational efficiency and lifespan of heat network equipment. Various factors affecting power quality, such as voltage fluctuations, harmonic distortions, and frequency variations, are scrutinized for their effects on the performance and durability of heat network components. Furthermore, potential solutions and strategies to mitigate the adverse effects of poor power quality on equipment reliability are discussed, underscoring the significance of proactive maintenance, monitoring systems, and technological advancements in bolstering the resilience of heat network infrastructures. Ultimately, this research sheds light on the pivotal role of power quality management in ensuring the efficient operation and longevity of heat network equipment, thereby contributing to the sustainability and resilience of energy systems.
Keywords: power quality; heat network equipment; reliability; voltage fluctuations; harmonic distortions; maintenance; monitoring systems; energy systems; sustainability